2010
DOI: 10.1002/lary.21415
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intranasal bevacizumab (Avastin) treatment in patients with hereditary hemorrhagic telangiectasia‐associated epistaxis

Abstract: In HHT patients intranasal Bevacizumab, applied as a topical spray or a submucosal injection, significantly improves epistaxis as measured by the Epistaxis Severity Score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
1
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 10 publications
3
97
1
6
Order By: Relevance
“…Patients were carefully followed for nasal cartilaginous septum perforations which have been described as a side effect of intravenous bevacizumab in cancer patients. [18][19][20][21] This complication was also described after bevacizumab submucosal injections 14,22 or laser treatments but never with topical treatments. In this study, nasal cartilaginous septum perforation was not observed following treatment administration.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Patients were carefully followed for nasal cartilaginous septum perforations which have been described as a side effect of intravenous bevacizumab in cancer patients. [18][19][20][21] This complication was also described after bevacizumab submucosal injections 14,22 or laser treatments but never with topical treatments. In this study, nasal cartilaginous septum perforation was not observed following treatment administration.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, several case reports and pilot studies reported a potential effect of bevacizumab nasal spray on epistaxis in HHT, with different doses and frequency of administration. 13,14,22,25 However, the frequency of epistaxis is highly variable in a given patient and between patients and it is currently not possible to conclude on efficacy based on those reports. We can hypothesize that a one-day treatment is not enough to act on epistaxis and that a single drug administration does not expose nasal mucosal tissue to bevacizumab in levels sufficient to improve epistaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its side effect profile includes spontaneous gastrointestinal perforation, cytopaenia, hypertension, delayed wound healing, septal perforation, weakness and haemorrhage, concerns about which have understandably limited its use for epistaxis alone; it is also expensive and long-term maintenance treatment is required as its effect is not permanent (58,79) . To try and mitigate these side effects, it has also been used intranasally, both as submucosal injections and in spray form (81)(82)(83)(84)(85)(86)(87)(88)(89)(90) . Whilst most authors report reasonable efficacy with no/minimal side effects, there have been concerns regarding the development of septal perforations following submucosal injection (81,83) .…”
Section: Antiangiogenic Therapymentioning
confidence: 99%
“…Whilst most authors report reasonable efficacy with no/minimal side effects, there have been concerns regarding the development of septal perforations following submucosal injection (81,83) . Most authors therefore advise against injecting bevacizumab over the cartilaginous septum (81,83,84,86) . The optimum dose and route of administration have not yet been found, although extended systemic dosing intervals (three-to four-weekly) and very low dose systemic bevacizumab have been suggested (91,92) .…”
Section: Antiangiogenic Therapymentioning
confidence: 99%